Genocide in Bosnia : the policy of "ethnic cleansing" - Cigar, Norman L. (Eastern European studies (College Station, Tex.), 1995)
"In this compelling and thorough study, Norman Cigar sets out to prove that genocide in Bosnia-Herzegovina is not simply the unintentional result of civil war or the unfortunate by-product of rabid nationalism. Genocide is, he contends, the planned and direct consequence of conscious policy decisions made by the Serbian establishment in Serbia and Bosnia-Herzegovina. Its policies were carried out in a deliberate and systematic manner as part of a broader strategy intended to achieve a defined political objective - the creation of an expanded, ethnically pure Greater Serbia." "Using testimony from congressional hearings, policy statements, interviews, and reports from the western and local media, the author describes a sinister policy of victimization that escalated from vilification to threats, then expulsion, torture, and killing. Cigar also takes the international community to task for its reluctance to act decisively and effectively." "Genocide in Bosnia provides a detailed account of the historical events, actions, and practices that led to and legitimated genocide in Bosnia-Herzegovina. It focuses attention not only on the horror of "ethnic cleansing" but on the calculated strategy that allowed it to happen. Cigar's book is important reading for anyone interested in the inherent violence of overzealous nationalism - from Rwanda to Afghanistan and anywhere else."--Jacket.